IMPROVING THE QUALITY OF HUMAN RESOURCES IN THE NORTH MOUNTAINOUS PROVINCE OF VIETNAM TO MEET BUSINESS DEMAND IN THE CONTEXT OF DIGITAL TRANSFORMATION - Hang NGUYEN THI (USV Annals of Economics and Public Administration, 2021)
Digital transformation in education is an inevitable and objective process to meet the high demand for human resources based on the change of methods and implementation methods. The training of high-quality human resources plays an extremely important and decisive role in the socio-economic development of each country. The change in training methods will put demands on changing methods, methods and techniques of teaching and training at universities. Research and pilot implementation at universities in the Northern Midlands and Mountains region of Vietnam. The development of higher education in the northern midland and mountainous provinces is reflected in the change in training models and methods, as well as the adjustment of training programs and objectives. This change follows a learner-centered approach to meet CDIO-oriented output standards. Thereby specifying the requirements that need to be implemented to improve the quality of human resources to meet the needs of enterprises. In the context of strong digital transformation, affecting the formation of digital businesses, it is necessary to have digital human resources to operate and master digital platform technologies. Therefore, the task of higher education is to equip learners with necessary professional knowledge, competencies and skills. That will help learners adapt to the changes and fluctuations of the working environment at organizations and businesses in the context of digital transformation.